The Legal Position Of Medical Informed Consent As A Means Of Legal Protection For Doctors and Patients - Suci Nazilla; Yusri Yusri; Suhaimi Suhaimi (International Journal of Law and Society, 2026)
Medical informed consent refers to a patient’s approval of a medical procedure after receiving adequate information regarding diagnosis, treatment objectives, risks, benefits, and available alternatives. The implementation of informed consent is regulated under Article 293 of Law Number 17 of 2023 concerning Health. However, in practice, informed consent is often treated merely as an administrative formality, which may lead to medical disputes and civil litigation. This study aims to analyze the legal position of informed consent from a civil law perspective, the legal protection afforded to both doctors and patients, and the legal consequences of medical actions performed without patient consent. This research employs a normative juridical method using statutory, conceptual, and case approaches through library research involving primary, secondary, and tertiary legal materials. The findings indicate that informed consent is an integral part of the therapeutic agreement establishing a civil legal relationship between doctors and patients and may serve as documentary evidence in civil proceedings. It provides legal protection for patients by ensuring their right to information and self-determination, while also protecting doctors as proof that medical actions were performed with consent. However, its evidentiary value is not absolute, as courts must also consider professional standards and medical negligence. This study concludes that informed consent must be implemented clearly, comprehensively, and based on the patient’s voluntary approval to ensure legal certainty and protection for all parties.